The development of a creative work rehabilitation organisation. Issue 1 (March 2023) - Leach, Jonathan; Agulnik, Peter; Armstrong, Neil
Work as therapy has a place in mental healthcare, but there is disagreement about how and why it might be helpful, and how best to conceptualise or represent those benefits. Over the last 50 years, occupational and industrial therapy sheltered workshops have been key elements in the provision of work activities in psychiatric settings, and community-based horticultural activities and creative craft work have offered additional approaches. Using archival material, interviews, witness seminars and personal reflections, this article charts the birth and initial growth of Restore, a charity providing creative work-based services in Oxfordshire between 1977 and 1988. Although Restore might be understood as a response to national trends in mental healthcare policy and research, its trajectory reflects local contingencies.